Single-cell analysis reveals the cellular and transcriptional heterogeneity of the normal pediatric thyroid - Reichenberger, Erin R.; Bambach, Nicholas E.; Spangler, Zachary; Ricarte-Filho, Julio C.; Hinkle, Kyle; Isaza, Amber; Bhatti, Tricia; Bauer, Andrew J.; Franco, Aime T. (Frontiers in Endocrinology, 2026)
To enhance the understanding of cellular heterogeneity within the pediatric thyroid, single-nuclei RNA sequencing was used to recover 38,069 non-pathogenic cells from thyroid tissue of three female pediatric/young adult patients. The recovered cells were analyzed using the SWANS (Single Entity Workflow ANalysiS pipeline (version 1.0). Analysis revealed seven major cell types: thyrocytes, endothelial cells, fibroblasts, C cells, T cells, B cells, and myeloid cells. Thyrocytes were the most prominent and heterogeneous cell type. Initially, two dominant thyrocyte subsets were identified based on transcriptional activity, which were subsequently subdivided into seven subclusters. Differentially expressed genes within each cluster support distinct cellular functions, including a metabolically active subset which may be involved in hormone synthesis and a subset involved in the transport of thyroid hormone into circulation. We identified an immune subpopulation originating predominantly from a single sample that was histologically and morphologically similar to the other two samples. This supports that transcriptional changes can be detected and used to identify populations of cells, even in the absence of histologically observable changes. This characterization represents the first comprehensive portraiture of pediatric thyroid gland cells and the first description of normal patient thyrocyte and stromal cell heterogeneity in the absence of adjacent malignancy.